Challenges of remote work practices - Peredia Parra, José Pablo (2023)
This thesis intends to understand the postures of employees of SAP SE on what they perceive their productivity to be like when working remotely. The approach of this research was performing qualitative interviews as the method of data collection for the purpose of getting a detailed view of their perception of how remote work has been a tool or a constraint for their productivity. The results of this thesis present how productivity has been perceived as better overall during the performance of the job tasks of the sample in the context of remote work. In addition, it is presented what they perceived as the challenges for them in this context (e.g, difficulties in adapting to remote work) and what they seem to like about working remotely that ultimately results in higher productivity for them (e.g. work-life balance and lack of commuting). It was concluded that in the majority of cases, productivity was affected positively by remote work even though most of the interviewees presented some difficulty while working remotely, as well as the majority of respondents preferred having a policy of hybrid work as for them, a balance between the office and remote work is ideal.